(untitled) (Bangladesh Journal of Botany, 2025)
A field experiment was conducted to compare the performance of inbred and hybrid rice ratooning influenced by cutting height and exogenous application of plant growth regulators (PGRs). Two rice cultivars viz. BRRI dhan28 (inbred) and BRRI hybrid dhan5 (hybrid); three stubble cutting heights viz. 5, 15 and 20 cm from ground; and four PGR treatments viz. control (spraying water), spraying 100 ppm auxin, 100 ppm gibberellin and 100 ppm gibberellin + 100 ppm auxin were set in a factorial design with three replications. Results revealed that ratooning with hybrid rice recorded higher yield (92.68%) and yield attributes (14.70% effective tiller, 18% total tiller, 15.29% panicle length, 26.01% filled grain and 16.82% 1000-grain weight) compared to inbred rice. Stubble cutting height of 15 cm along with application of 100 ppm gibberellin + 100 ppm auxin resulted in highest yield and yield attributes. Therefore, the study concluded that hybrid rice was capable to produce higher ratoon yield than inbred rice maintaining 15 cm stubble cutting height along with PGRs application. Bangladesh J. Bot. 54(4): 987-993, 2025 (December)